The Battle of the Golden Spurs (Courtrai, 11 July 1302) : a contribution to the history of Flanders' war of liberation, 1297-1305 - Verbruggen, J. F. (Warfare in history., 2002)
On 11 July 1302, beneath the town walls of Courtrai, the most splendid army of knights in Christendom, the flower of French nobility, was utterly defeated by Flemish rebels, common workers and peasants. The superbly trained noblemen, who had devoted their whole life to the military profession, fully experienced in fighting on horseback in close ranks, were led by an able commander, the count of Artois, victor of a number of campaigns.